Synergistic Tumoricidal Effects of Alpha-Lipoic Acid and Radiotherapy on Human Breast Cancer Cells via HMGB1 - Choi, Hoon Sik; Kim, Jin Hyun; Jang, Si Jung; Yun, Jeong Won; Kang, Ki Mun; Jeong, Hojin; Ha, In Bong; Jeong, Bae Kwon (Cancer research and treatment, 2021)
Purpose Radiotherapy (RT) is one of main strategies of cancer treatment. However, some cancer cells are resistant to radiation-induced cell death, including apoptosis. Therefore, alternative approaches targeting different anti-tumor mechanisms such as cell senescence are required. This study aimed to investigate the synergistic effect of alpha-lipoic acid (ALA) on radiation-induced cell death and senescence in MDA-MB-231 human breast cancer cells.Materials and Methods The cells were divided into four groups depending on the cell treatment (control, ALA, RT, and ALA+RT). Cells were analyzed for morphology, apoptotic cell death, mitochondrial reactive oxygen species, membrane potential, cellular senescence, and cell cycle.Results Our data showed that ALA significantly promoted apoptotic cell death when combined with RT, as reflected by Annexin V staining, expression of apoptosis-related factors, mitochondrial damages as well as cell morphological changes and reduction of cell numbers. In addition, ALA significantly enhanced radiation-induced cellular senescence, which was shown by increased HMGB1 expression in the cytosol fraction compared to the control, increased p53 expression compared to the control, activation of p38 as well as nuclear factor кB, and G2/M cell cycle arrest.Conclusion The current study is the first report showing a new mode of action (senescence induction) of ALA beyond apoptotic cell death in MDA-MB-231 cancer cells known to be resistant to RT.